Tretan Muslim Dark Jokes: A Critical Study on Summon Podcast Content - Mawardi, Imam; Hidayatullah, Ahmad Fauzan; Octafiani, Tri Utami (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
The Somasi event on Deddy Corbuzier's Youtube channel is a stand-up comedy show on Youtube. The comedy material is called dark jokes. From the Dark Jokes that Tretan Muslims conveyed about religion in the show, this article attempts to analyse the value of tolerance internalised in comedy. This research focused on one video upload in a summon event entitled "Tretan Muslim Penista Di Somasi!" This research uses a descriptive-qualitative method with Norman Fairclough's critical discourse analysis, namely the analysis of video texts and discourse as social praxis. The analysis is carried out by reviewing the discourse conveyed in the video text, and how it affects social media users, through an analysis of 1678 comments from the audience. It was found, (1) that the background and social environment of Tretan influenced the construction of the discourse constructed as well as the purpose of the discourse. (2) There are messages of tolerance and diversity in the material presented by Tretan Muslim in his dark jokes. (3) The discourse affects the audience so that it has a positive and negative response. Several comments show indications of tolerant and intolerant values.